If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + -7 = x + 19 Reorder the terms: -7 + X = x + 19 Reorder the terms: -7 + X = 19 + x Solving -7 + X = 19 + x Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '7' to each side of the equation. -7 + 7 + X = 19 + 7 + x Combine like terms: -7 + 7 = 0 0 + X = 19 + 7 + x X = 19 + 7 + x Combine like terms: 19 + 7 = 26 X = 26 + x Simplifying X = 26 + x
| 3w+3x=99 | | 3k^2-12k+12=75 | | -20+4x=43+x | | 2w+1x=49 | | 3k(k+1)=0 | | 9x-2=6x+13 | | 2x^2-5x-3=-3 | | 2x-5y+5xy=14 | | 2xy-5y+5xy=14 | | 36x-54+49=0 | | 2x^4/6x^2 | | y=32x+2 | | y=22x+1 | | 22=ax+1 | | 16-3x=36-8x | | 2x+7=19-2x | | 5ab+3ba= | | x/=6 | | so/ve | | y=x^3+9x-1 | | 3x+11=-17-4x | | 28p=70 | | 0.16x=1 | | f(x)=x^3-x^2+8x | | 80d=60 | | 8x-20=4x+8 | | Y=(10*7+90) | | (x/1.70)=8.37 | | 0.35*0.20= | | 4kx^2-5x+3k=0 | | 2p^2+2p+1=0 | | 2.5(x-20)=2.3x+8 |